Pelestarian Kesenian Sandur Sekar Arum di Desa Sukorejo Kecamatan Parengan Kabupaten Tuban 2005-2018 - Amalia Juwita Kusuma; Artono A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Sandur is a traditional performing art rooted in the agrarian communities of Tuban Regency, representing significant historical, cultural, and local identity values. Amid the challenges posed by modernization, the continuity of Sandur requires systematic preservation efforts to ensure its sustainability while adapting to contemporary social changes. This study aims to analyze the historical development of Sandur Sekar Arum in Sukorejo Village, examine the preservation efforts undertaken between 2005 and 2018, explore its development as a cultural tourism attraction, and identify its impacts on the local community. This research employs the historical research method, consisting of heuristics, internal source criticism, interpretation, and historiography. Data were collected through interviews with artists and community leaders, documentation, literature review, and relevant written sources. The findings indicate that Sandur Sekar Arum originated from the agrarian traditions of the local community and was transmitted across generations before becoming more systematically managed beginning in 2005. Preservation has been carried out through artist regeneration, regular rehearsals, cultural performances, art festivals, and support from both the local community and the village government. These efforts have contributed to the transformation of Sandur into a cultural tourism attraction that reinforces the cultural identity of Sukorejo Village. Furthermore, the preservation of Sandur has generated positive social and cultural impacts by strengthening community participation, preserving local cultural values, and reinforcing local identity. It has also contributed to the local economy by creating business opportunities during cultural events.